Effectiveness of Ethnomathematics Application in Geometry Mathematics Learning - Parmiyanti, Anju; Rismawati (CV. Generasi Insan Rafflesia, 2023)
The application of ethnomathematics in elementary school in the learning process often encounters obstacles, especially for the students themselves, where students are still constrained by abstract things. One of the abstract branches of mathematics taught in schools is Geometry. Geometry is part of what is studied in mathematics lessons. One alternative in learning geometry is to blend in with the culture in the student's own environment. Mathematics learning that is connected to existing culture is called ethnomathematics. The culture that can be connected to mathematics, especially geometry material, is Acehnese culture which contains geometric concepts in it. The aim of this research is to determine the effectiveness of applying ethnomathematics in learning mathematics, geometry material for class III students at SD Negeri 4 Kuala Bate. This research uses a quantitative approach with a one-group posttest only experimental research type. data collection techniques through written tests. The subject of this research involved 18 students. Quantitative data was analyzed using descriptive analysis and using the one sample t-test. The results of the research show that the application of ethnomathematics in teaching mathematics about geometry material in class III of SD Negeri 4 Kuala Bate is effective in increasing students' understanding of geometry material. This is based on the classical completeness results of 88.9% and the results of the paired sample t-test which shows that there is a increase in student learning outcome by using ethnomathematics based learning. So it can be concluded that the aplication of ethnomathematics in learning mathematic with geometry material is effective for class III student at SD Negeri 4 Kuala Bate.